Direct writing of gold nanostructures with an electron beam: On the way to pure nanostructures by combining optimized deposition with oxygen-plasma treatment - Belić, Domagoj; Shawrav, Mostafa M.; Bertagnolli, Emmerich; Wanzenboeck, Heinz D. (Beilstein Journal of Nanotechnology, 2017)
This work presents a highly effective approach for the chemical purification of directly written 2D and 3D gold nanostructures suitable for plasmonics, biomolecule immobilisation, and nanoelectronics. Gold nano- and microstructures can be fabricated by one-step direct-write lithography process using focused electron beam induced deposition (FEBID). Typically, as-deposited gold nanostructures suffer from a low Au content and unacceptably high carbon contamination. We show that the undesirable carbon contamination can be diminished using a two-step process – a combination of optimized deposition followed by appropriate postdeposition cleaning. Starting from the common metal-organic precursor Me2-Au-tfac, it is demonstrated that the Au content in pristine FEBID nanostructures can be increased from 30 atom % to as much as 72 atom %, depending on the sustained electron beam dose. As a second step, oxygen-plasma treatment is established to further enhance the Au content in the structures, while preserving their morphology to a high degree. This two-step process represents a simple, feasible and high-throughput method for direct writing of purer gold nanostructures that can enable their future use for demanding applications.
Keywords: FEBID; gold nanostructures; oxygen plasma; postdeposition purification

(untitled) - Fowlkes, J. D.; Winkler, R.; Lewis, B. B.; Stanford, M. G.; Plank, H.; Rack, P. D. (ACS Nano, 2016)

(untitled) - Jesse, S.; Borisevich, A. Y.; Fowlkes, J. D.; Lupini, A. R.; Rack, P. D.; Unocic, R. R.; Sumpter, B. G.; Kalinin, S. V.; Belianinov, A.; Ovchinnikova, O. S. (ACS Nano, 2016)

(untitled) - Gavagnin, M.; Wanzenboeck, H. D.; Wachter, S.; Shawrav, M. M.; Persson, A.; Gunnarsson, K.; Svedlindh, P.; Stöger-Pollach, M.; Bertagnolli, E. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Winkler, R.; Schmidt, F.-P.; Haselmann, U.; Fowlkes, J. D.; Lewis, B. B.; Kothleitner, G.; Rack, P. D.; Plank, H. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Lewis, B. B.; Winkler, R.; Sang, X.; Pudasaini, P. R.; Stanford, M. G.; Plank, H.; Unocic, R. R.; Fowlkes, J. D.; Rack, P. D. (Beilstein J. Nanotechnol., 2017)

(untitled) - van Dorp, W. F.; Zhang, X.; Feringa, B. L.; Hansen, T. W.; Wagner, J. B.; De Hosson, J. T. M. (ACS Nano, 2012)

(untitled) - van Dorp, W. F.; van Someren, B.; Hagen, C. W.; Kruit, P. (Nano Lett., 2005)

(untitled) - Wnuk, J. D.; Rosenberg, S. G.; Gorham, J. M.; van Dorp, W. F.; Hagen, C. W.; Fairbrother, D. H. (Surf. Sci., 2011)

(untitled) - Utke, I.; Hoffmann, P.; Melngailis, J. (J. Vac. Sci. Technol., B, 2008)

(untitled) - van Dorp, W. F.; Hagen, C. W. (J. Appl. Phys., 2008)

(untitled) - de Teresa, J. M.; Fernández-Pacheco, A.; Córdoba, R.; Serrano-Ramón, L.; Sangiao, S.; Ibarra, M. R. (J. Phys. D: Appl. Phys., 2016)

(untitled) - Serrano-Ramón, L.; Córdoba, R.; Rodríguez, L. A.; Magén, C.; Snoeck, E.; Gatel, C.; Serrano, I.; Ibarra, M. R.; De Teresa, J. M. (ACS Nano, 2011)

(untitled) - Fernández-Pacheco, A.; Serrano-Ramón, L.; Michalik, J. M.; Ibarra, M. R.; De Teresa, J. M.; O'Brien, L.; Petit, D.; Lee, J.; Cowburn, R. P. (Sci. Rep., 2013)

(untitled) - Franken, J. H.; van der Heijden, M. A. J.; Ellis, T. H.; Lavrijsen, R.; Daniels, C.; McGrouther, D.; Swagten, H. J. M.; Koopmans, B. (Adv. Funct. Mater., 2014)

(untitled) - Gavagnin, M.; Wanzenboeck, H. D.; Belić, D.; Bertagnolli, E. (ACS Nano, 2013)

(untitled) - Winhold, M.; Weirich, P. M.; Schwalb, C. H.; Huth, M. (Appl. Phys. Lett., 2014)

(untitled) - Murakami, K.; Takai, M. (Microelectron. Eng., 2015)

(untitled) - Dukic, M.; Winhold, M.; Schwalb, C. H.; Adams, J. D.; Stavrov, V.; Huth, M.; Fantner, G. E. (Nat. Commun., 2016)

(untitled) - Peinado, P.; Sangiao, S.; De Teresa, J. M. (ACS Nano, 2015)

(untitled) - Kim, S.; Russell, M.; Kulkarni, D. D.; Henry, M.; Kim, S. S.; Naik, R. R.; Voevodin, A. A.; Jang, S. S.; Tsukruk, V. V.; Fedorov, A. G. (ACS Nano, 2016)

(untitled) - Cagliani, A.; Lindvall, N.; Larsen, M. B. B. S.; MacKenzie, D. M. A.; Jessen, B. S.; Booth, T. J.; Bøggild, P. (Nanoscale, 2015)

(untitled) - Kim, S.; Russell, M.; Henry, M.; Kim, S. S.; Naik, R. R.; Voevodin, A. A.; Jang, S. S.; Tsukruk, V. V.; Fedorov, A. G. (Nanoscale, 2015)

(untitled) - Kim, S.; Kulkarni, D. D.; Davis, R.; Kim, S. S.; Naik, R. R.; Voevodin, A. A.; Russell, M.; Jang, S. S.; Tsukruk, V. V.; Fedorov, A. G. (ACS Nano, 2014)

(untitled) - Shen, X.; Wang, H.; Yu, T. (Nanoscale, 2013)

(untitled) - Fisher, J. S.; Kottke, P. A.; Kim, S.; Fedorov, A. G. (Nano Lett., 2015)

(untitled) - Bresin, M.; Chamberlain, A.; Donev, E. U.; Samantaray, C. B.; Schardien, G. S.; Hastings, J. T. (Angew. Chem., Int. Ed., 2013)

(untitled) - Schardein, G.; Donev, E. U.; Hastings, J. T. (Nanotechnology, 2011)

(untitled) - Donev, E. U.; Schardein, G.; Wright, J. C.; Hastings, J. T. (Nanoscale, 2011)

(untitled) - Roberts, N. A.; Fowlkes, J. D.; Magel, G. A.; Rack, P. D. (Nanoscale, 2013)

(untitled) - Webb, J. A.; Bardhan, R. (Nanoscale, 2014)

(untitled) - Mølhave, K.; Madsen, D. N.; Dohn, S.; Bøggild, P. (Nanotechnology, 2004)

(untitled) - Utke, I.; Dwir, B.; Leifer, K.; Cicoira, F.; Doppelt, P.; Hoffmann, P.; Kapon, E. (Microelectron. Eng., 2000)

(untitled) - Koops, H. W. P.; Schossler, C.; Kaya, A.; Weber, M. (J. Vac. Sci. Technol., B, 1996)

(untitled) - Woźniak, P.; Höflich, K.; Brönstrup, G.; Banzer, P.; Christiansen, S.; Leuchs, G. (Nanotechnology, 2016)

(untitled) - Esposito, M.; Tasco, V.; Cuscunà, M.; Todisco, F.; Benedetti, A.; Tarantini, I.; Giorgi, M.; Sanvitto, D.; Passaseo, A. (ACS Photonics, 2015)

(untitled) - Höflich, K.; Becker, M.; Leuchs, G.; Christiansen, S. (Nanotechnology, 2012)

(untitled) - Utke, I.; Jenke, M. G.; Roling, C.; Thiesen, P. H.; Iakovlev, V.; Sirbu, A.; Mereuta, A.; Caliman, A.; Kapon, E. (Nanoscale, 2011)

(untitled) - Höflich, K.; Yang, R. B.; Berger, A.; Leuchs, G.; Christiansen, S. (Adv. Mater., 2011)

(untitled) - Graells, S.; Aćimović, S.; Volpe, G.; Quidant, R. (Plasmonics, 2010)

(untitled) - Graells, S.; Alcubilla, R.; Badenes, G.; Quidant, R. (Appl. Phys. Lett., 2007)

(untitled) - Shawrav, M. M.; Wanzenboeck, H. D.; Belić, D.; Gavagnin, M.; Bethge, O.; Schinnerl, M.; Bertagnolli, E. (Phys. Status Solidi A, 2014)

(untitled) - Hochleitner, G.; Steinmair, M.; Lugstein, A.; Roediger, P.; Wanzenboeck, H. D.; Bertagnolli, E. (Nanotechnology, 2011)

(untitled) - Mølhave, K.; Madsen, D. N.; Rasmussen, A. M.; Carlsson, A.; Appel, C. C.; Brorson, M.; Jacobsen, C. J. H.; Bøggild, P. (Nano Lett., 2003)

(untitled) - Folch, A.; Tejada, J.; Peters, C. H.; Wrighton, M. S. (Appl. Phys. Lett., 1995)

(untitled) - van Dorp, W. F.; Wu, X.; Mulders, J. J. L.; Harder, S.; Rudolf, P.; De Hosson, J. T. M. (Langmuir, 2014)

(untitled) - Mulders, J. J. L.; Veerhoek, J. M.; Bosch, E. G. T.; Trompenaars, P. H. F. (J. Phys. D: Appl. Phys., 2012)

(untitled) - Klein, K. L.; Randolph, S. J.; Fowlkes, J. D.; Allard, L. F.; Meyer, H. M., III; Simpson, M. L.; Rack, P. D. (Nanotechnology, 2008)

(untitled) - Henry, M. R.; Kim, S.; Fedorov, A. G. (J. Phys. Chem. C, 2016)

(untitled) - Begun, E.; Dobrovolskiy, O. V.; Kompaniiets, M.; Sachser, R.; Gspan, C.; Plank, H.; Huth, M. (Nanotechnology, 2015)

(untitled) - Stanford, M. G.; Lewis, B. B.; Noh, J. H.; Fowlkes, J. D.; Rack, P. D. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Stanford, M. G.; Lewis, B. B.; Noh, J. H.; Fowlkes, J. D.; Roberts, N. A.; Plank, H.; Rack, P. D. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Mehendale, S.; Mulders, J. J. L.; Trompenaars, P. H. F. (Nanotechnology, 2013)

(untitled) - Geier, B.; Gspan, C.; Winkler, R.; Schmied, R.; Fowlkes, J. D.; Fitzek, H.; Rauch, S.; Rattenberger, J.; Rack, P. D.; Plank, H. (J. Phys. Chem. C, 2014)

(untitled) - Plank, H.; Noh, J. H.; Fowlkes, J. D.; Lester, K.; Lewis, B. B.; Rack, P. D. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Perez-Roldan, M. J.; Mulders, J. J. L.; Trompenaars, P. H. F. (J. Phys. D: Appl. Phys., 2017)

(untitled) - Villamor, E.; Casanova, F.; Trompenaars, P. H. F.; Mulders, J. J. L. (Nanotechnology, 2015)

(untitled) - Fowlkes, J. D.; Geier, B.; Lewis, B. B.; Rack, P. D.; Stanford, M. G.; Winkler, R.; Plank, H. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Aaltonen, T.; Ritala, M.; Sajavaara, T.; Keinonen, J.; Leskelä, M. (Chem. Mater., 2003)

(untitled) - Mackus, A. J. M.; Garcia-Alonso, D.; Knoops, H. C. M.; Bol, A. A.; Kessels, W. M. M. (Chem. Mater., 2013)

(untitled) - Griffiths, M. B. E.; Pallister, P. J.; Mandia, D. J.; Barry, S. T. (Chem. Mater., 2016)

(untitled) - Mäkelä, M.; Hatanpää, T.; Mizohata, K.; Räisänen, J.; Ritala, M.; Leskelä, M. (Chem. Mater., 2017)

(untitled) - Riazanova, A. V.; Rikers, Y. G. M.; Mulders, J. J. L.; Belova, L. M. (Langmuir, 2012)

(untitled) - Botman, A.; Mulders, J. J. L.; Weemaes, R.; Mentink, S. (Nanotechnology, 2006)

(untitled) - Mehendale, S.; Mulders, J. J. L.; Trompenaars, P. H. F. (Microelectron. Eng., 2015)

(untitled) - Belić, D.; Shawrav, M. M.; Gavagnin, M.; Stöger-Pollach, M.; Wanzenboeck, H. D.; Bertagnolli, E. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Haverkamp, C.; Höflich, K.; Jäckle, S.; Manzoni, A.; Christiansen, S. (Nanotechnology, 2017)

(untitled) - Mansilla, C.; Mehendale, S.; Mulders, J. J. L.; Trompenaars, P. H. F. (Nanotechnology, 2016)

(untitled) - Shawrav, M. M.; Taus, P.; Wanzenboeck, H. D.; Schinnerl, M.; Stöger-Pollach, M.; Schwarz, S.; Steiger-Thirsfeld, A.; Bertagnolli, E. (Sci. Rep., 2016)

(untitled) - Wnuk, J. D.; Gorham, J. M.; Rosenberg, S. G.; van Dorp, W. F.; Madey, T. E.; Hagen, C. W.; Fairbrother, D. H. (J. Appl. Phys., 2010)

(untitled) - Wnuk, J. D.; Gorham, J. M.; Rosenberg, S. G.; Madey, T. E.; Hagen, C. W.; Fairbrother, D. H. (J. Vac. Sci. Technol., B, 2010)

(untitled) - Córdoba, R.; Sharma, N.; Kölling, S.; Koenraad, P. M.; Koopmans, B. (Nanotechnology, 2016)

(untitled) - Rack, P. D.; Fowlkes, J. D.; Randolph, S. J. (Nanotechnology, 2007)

(untitled) - Fowlkes, J. D.; Rack, P. D. (ACS Nano, 2010)

(untitled) - Bret, T.; Utke, I.; Hoffmann, P. (Microelectron. Eng., 2005)

(untitled) - Winkler, R.; Fowlkes, J.; Szkudlarek, A.; Utke, I.; Rack, P. D.; Plank, H. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Miyazoe, H.; Utke, I.; Kikuchi, H.; Kiriu, S.; Friedli, V.; Michler, J.; Terashima, K. (J. Vac. Sci. Technol., B, 2010)

(untitled) - Plank, H.; Smith, D. A.; Haber, T.; Rack, P. D.; Hofer, F. (ACS Nano, 2011)

(untitled) - Fowlkes, J. D.; Doktycz, M. J.; Rack, P. D. (Nanotechnology, 2010)

(untitled) - Burbridge, D. J.; Gordeev, S. N. (Nanotechnology, 2009)

(untitled) - Love, C. J.; Estroff, L. A.; Kriebel, J. K.; Nuzzo, R. G.; Whitesides, G. M. (Chem. Rev., 2005)

(untitled) - Kitajima, T.; Nakashima, J.; Nakano, T.; Makabe, T. (Thin Solid Films, 2006)

(untitled) - Taylor, K. J.; Tynan, G. R. (J. Vac. Sci. Technol., A, 2005)